Loc-hollow Fuzzy Modules with Related Modules - Kharbeet, Shaheed Jameel; Khalf, Hatam Yahya (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2022)
The concept of a small f- subm was presented in a previous study. This work introduced a concept of a hollow f- module, where a module is said to be hollow fuzzy when every subm of it is a small f- subm. Some new types of hollow modules are provided namely, Loc- hollow f- modules as a strength of the hollow module, where every Loc- hollow f- module is a hollow module, but the converse is not true. Many properties and characterizations of these concepts are proved, also the relationship between all these types is researched. Many important results that explain this relationship are demonstrated also several characterizations and properties related to these concepts are given.